2017
DOI: 10.5455/ijmrcr.surgical-management-traumatic-manubrio-sternal-dislocation
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Traumatic Manubrio-Sternal Dislocation With Locking Compression Plate; A Case Report and Review of Literature.

Abstract: Background: Manubriosternal joint dislocation as a result of trauma is rare with only few case reports published in the literature. Materials that have been used for fixation of displaced manubriosternal joint are steel wires, polydioxanone ropes, and plates with screws. Case: We present a case of manubriosternal dislocation in which fixation was done with locking compression plate. It is a case of 32-years-old lady with a history of road traffic accident; car ran over her chest. She had multiple bilateral rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…[4] Manubriosternal dislocations are a rare occurrence, representing 17.6% of lesions of the sternum, corresponding to <0.5% of all traumatic lesions. [1][2][3]5] Of 250 fatal road accidents, this type of lesion was observed in 13 patients, and was associated with fracture of the thoracic spine in just 3 individuals. [2] Fowler et al [6] reported 21 patients with dislocation fractures of the sternum, in 9 of whom fractures of the thoracic vertebrae were diagnosed.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…[4] Manubriosternal dislocations are a rare occurrence, representing 17.6% of lesions of the sternum, corresponding to <0.5% of all traumatic lesions. [1][2][3]5] Of 250 fatal road accidents, this type of lesion was observed in 13 patients, and was associated with fracture of the thoracic spine in just 3 individuals. [2] Fowler et al [6] reported 21 patients with dislocation fractures of the sternum, in 9 of whom fractures of the thoracic vertebrae were diagnosed.…”
Section: Epidemiologymentioning
confidence: 99%
“…Various operative procedures using plates, wire loops, Kirschner wires or polydioxanone loops have been described in the literature. [1,22] Schmitz et al [23] report a resection arthroplasty for luxation of the manubriosternal joint in rheumatoid arthritis, with success. The excision of a manubriosternal synchondrosis already damaged by a traumatic event, and the cuneiform chondrectomy of the third and fourth rib cartilage bilaterally, was the technique used by Divisi et al, [24] with an acceptable outcome.…”
Section: Indications For Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation